A parallel second-order unstructured finite volume method for 3D free-surface flows using a σ coordinate - Uh Zapata, Miguel; Zhang, Wei; Pham Van Bang, Damien; Nguyen, Kim Dan (Computers & Fluids, 2019)
Keywords: PhamVanBang_Damien

Effect of Scour on the Natural Frequency Responses of Bridge Piers: Development of a Scour Depth Sensor - Boujia, Nissrine; Schmidt, Franziska; Chevalier, Christophe; Siegert, Dominique; Pham Van Bang, Damien (Infrastructures, 2019)
Local scour is the removal of soil around bridge foundations under the erosive action of flowing water. This hydraulic risk has raised awareness of the need for developing continuous monitoring techniques to estimate scour depth around bridge piers and abutments. One of the emerging techniques is based on monitoring the vibration frequency of either bridge piers or a driven sensor in the riverbed. The sensor proposed in this study falls into the second category. Some unresolved issues are investigated: the effect of the geometry and material of the sensor, the effect of the embedded length and the effect of soil type. To this end, extensive laboratory tests are performed using rods of different materials, with various geometries and lengths. These tests are conducted in both dry sand and a soft clayey soil. Since the sensor will be placed in the riverbed, it is crucial to evaluate the effect of immersed conditions on its response. A numerical 3D finite-element model was developed and compared against experimental data. This model was then used to compute the ‘wet’ frequencies of the sensor. Finally, based on both the experimental and numerical results, an equivalent cantilever model is proposed to correlate the variation of the frequency of the sensor to the scour depth.
Keywords: PhamVanBang_Damien

Numerical Study of Alternate Bars in Alluvial Channels With Nonuniform Sediment - Cordier, F.; Tassi, P.; Claude, N.; Crosato, A.; Rodrigues, S.; Pham Van Bang, D. (Water Resources Research, 2019)
Abstract Rivers typically present heterogeneous bed material, but the effects of sediment nonuniformity on river bar characteristics are still unclear. This work investigates the impact of sediment size heterogeneity on alternate bars with a morphodynamic numerical model. The model is first used to reproduce a laboratory experiment showing alternate bar formation with nonuniform bed material. Subsequently, the influence of sediment size heterogeneity on alternate bars is investigated distinguishing hybrid from free bars, definition based on the presence/absence of morphodynamic forcing, considering the results of nine scenarios. In four of them, a transverse obstacle is used to generate forcing. The computations are carried out with the Telemac‐Mascaret system solving the two‐dimensional shallow‐water equations with a finite element approach, accounting for horizontal and vertical sediment sorting processes. The results show that sediment heterogeneity affects free migrating and hybrid bars in a different way. The difference lies in the presence/absence of a migration front, so that distinct relations between bed topography, bed shear stress, and sediment sorting are obtained. Sediment sorting and associated planform redistribution of bed roughness only slightly modify free migrating bar morphodynamics, whereas hybrid bars are greatly impacted, with decreased amplitude and increased wavelength. Increased sediment size heterogeneity increases the degree of sediment sorting, while the sorting pattern remains the same for both free and hybrid bars. Moreover, it produces averagely higher, longer, and faster free bars, while in the case of hybrid bars their wavelength is increased but no general trend can be determined for their amplitude. , Key Points Free bars and hybrid bars show distinct topography, bed shear stress, sediment transport, and sediment sorting patterns Increased sediment heterogeneity induces longer free/hybrid bars, higher free bars but no general trend for the hybrid bar amplitude Sediment sorting does not impact the averaged free bar characteristics, while hybrid bars become longer and damped
Keywords: PhamVanBang_Damien